Women and Activists: Constructing Old Age in Patchwork Narratives - Mazzucchelli, Nicole (2021)
Discourses on the aging of older women have focused on the problems and difficulties they face, omitting the recognition of their resources and potential. This research reports the results of a research that rescues the meanings of aging of women activists of the Agrupación Bordadoras por la Memoria —embroiderers’ group for memory—, in Chile. From feminist gerontology and narrative perspective, we produce patchwork narratives that offer new versions of being older. The results show the emergence of narratives on pandemic old age, gender distinctions, the wisdom acquired at this stage, and their experience of aging from political action, questioning the characteristics with which old women are traditionally described. It is concluded that the exercise of construction and questioning that the participants carry out in front of their own old age from their associative experience, allows them to tense and dispute positions, transgressing the normative representation of hegemonic old age.